Dielectric Characterization of Costal Cartilage Chondrocytes - Stacey, Michael W. (2013)
BACKGROUND: Chondrocytes respond to biomechanical and bioelectrochemical stimuli by secreting appropriate extracellular matrix proteins that enables the tissue to withstand the large forces it experiences. Although biomechanical aspects of cartilage are well described, little is known of the bioelectrochemical responses. The focus of this study is to identify bioelectrical characteristics of human costal cartilage cells using dielectric spectroscopy. METHODS: Dielectric spectroscopy allows non-invasive probing of biological cells. An in house computer program is developed to extract dielectric properties of human costal cartilage cells from raw cell suspension impedance data measured by a microfluidic device. The dielectric properties of chondrocytes are compared with other cell types in order to comparatively assess the electrical nature of chondrocytes. RESULTS: The results suggest that electrical cell membrane characteristics of chondrocyte cells are close to cardiomyoblast cells, cells known to possess an array of active ion channels. The blocking effect of the non-specific ion channel blocker gadolinium is tested on chondrocytes with a significant reduction in both membrane capacitance and conductance. CONCLUSIONS: We have utilized a microfluidic chamber to mimic biomechanical events through changes in bioelectrochemistry and described the dielectric properties of chondrocytes to be closer to cells derived from electrically excitably tissues GENERAL SIGNIFICANCE AND INTEREST: The studydescribes dielectric characterization of human costal chondrocyte cells using physical tools, where results and methodology can be used to identify potential anomalies in bioelectrochemical responses that may lead to cartilage disorders.